Modeling traumatic brain and neural injuries: insights from zebrafish - Murashova, Lada; Dyachuk, Vyacheslav (Frontiers in Molecular Neuroscience, 2025)
A traumatic injury to the nervous system has significant consequences for mammals, including long-term disability, loss of functions, and neuropathic pain. In contrast to mammals, zebrafish (Danio rerio) exhibits a markedly enhanced neuroregenerative capacity, which can be attributed to the phenomenon of adult neurogenesis and to the distinctive characteristics of the inflammatory response at the injury site. The post-traumatic recovery of zebrafish under different experimental injury conditions was demonstrated in numerous studies, which has substantially advanced our understanding of the cellular and molecular mechanisms of neuroregeneration in this animal. In view of the significant differences in molecular mechanisms depending on the injury site, lesion severity, and harmful agents, selecting an appropriate model for investigations is of paramount importance. This review discusses some approaches to modeling neural injury in zebrafish and considers the effect of cellular interactions in post-traumatic neurogenesis, with focus on the animal’s age and the specific damaging factor that may be used to select an optimum model for certain nervous system lesions.